METABOLİK SENDROMLU HASTALARDA PARAOKSONAZ 1 AKTİVİTELERİ VE FENOTİPLERİNİN ARAŞTIRILMASI - TÜRKOĞLU, SEMRA (Fırat Üniveristesi, 2006)
METABOLİK SENDROMLU HASTALARDA PARAOKSONAZ 1AKTİVİTELERİ VE FENOTİPLERİNİN ARAŞTIRILMASISEMRA TÜRKOĞLUÖZETMetabolik sendrom, insülin direncinin ile oluşan metabolikdüzensizliklerin bir grubudur. Metabolik sendromun yaygınlığı gün geçtikçeartmaktadır ve bazı araştırmalara göre son 5 yılda %100 oranında artmıştır.Dislipidemi, abdominal obezite, yüksek kan basıncı, prediyabet ve serum HDLdüzeylerindeki düşüklük metabolik sendromun önemli komponentleridir. Genetik,yaşam tarzı ve çevresel faktörler de metabolik sendromun artışında önemli bir rolesahip olabilir. İnsülin rezistansına bağlı gelişen metabolik değişikliklerdenkaynaklanan oksidatif stresin metabolik sendromun komplikasyonlarınınoluşmasına katkıda bulunmaktadır.Paraoksonaz (PON1) yüksek dansiteli lipoprotein (HDL) ile ilişkiliantioksidan bir enzimdir. Düşük PON1'in, dislipidemi, diabetes mellitus, ilerlemişyaş, hipertansiyon, düşük HDL-kolesterol seviyesi ve artmış oksidatif stresleilişkili olduğu gösterilmiştir. Bu tez çalışmasında metabolik sendromlu hastalarınserum Paraoksonaz (PON1) ve Arilesteraz (ARE) aktivite düzeyleri ile totalkolesterol, trigliserid, LDL, HDL, VLDL, glukoz, insülin, ürik asit, C-peptit,AST, ALT, GGT ve tam kanda Hb, Htc, PLT düzeyleri ölçülmüş ve metaboliksendrom tanı kriterleri ile serum PON1 aktivite düzeyleri arasındaki ilişkiincelenerek PON1 aktivitesinin metabolik sendromun bir parçası olup olmadığıaraştırılmıştır. Metabolik sendromlu hastalarda PON1 aktivitesi ve fenotipleri ilkkez bu çalışmada gösterilmiştir.Metabolik sendromlu hastalarda serum PON1 aktivitesi metaboliksendromlu olmayan bireylerdeki serum PON 1 aktivitesine göre anlamlı olarakdaha düşük (p<0.05), HDL hariç lipid düzeyleri anlamlı olarak daha yüksekbulunmuştur (p<0.05). MES'li hastaların serum glukoz, total kolesterol, LDL,VLDL, trigliserid, GGT, ürik asit, insülin, C-peptid, VKİ, sistolik kan basıncı vebel çevresi değerleri kontrol grubuna göre yüksek, HDL-kolesterol değeri iseanlamlı olarak düşük bulunmuştur (p<0.05). Fenotipleri belirlemede PON1/AREaktivitelerinin kümülatif oranları belirlenerek 3 fenotipin varlığı gösterilmiştir.Sonuç olarak, bu çalışmada metabolik sendromlu hastalarda daha düşükantioksidan PON1 enzimatik aktivitesi, artmış lipid düzeyleri, HDL-kolesteroldeki azalma ve artan glukoz düzeyleri ile anlamlı bir ilişki bulunmasımetabolik sendromun erken tanı ve tedavisinde önemli yer tutabilir.Anahtar Kelimeler: Metabolik Sendrom, Paraoksonaz, Arilesteraz, Fenotip.

INVESTIGATION OF PARAOXONASE 1 ACTIVITIES ANDPHENOTYPES IN PATIENTS WITH METABOLIC SYNDROMESEMRA TÜRKOĞLUABSTRACTMetabolic syndrome is a constellation of metabolic disorders that existswith insulin resistance. The prevalence of the metabolic syndrome is increasingday by day, and some evidence indicates that it has risen at the rate of %100 inratio in the 5 last years. Dyslipidemia, abdominal obesity, high blood pressure,diabetes mellitus and decrease in serum HDL levels are important componentsin the pathogenesis of the metabolic syndrome. Genetics, lifestyle, andenvironmental factors may also have a significans in the increase of metabolicsyndrome. There is that the degree of metabolic syndrome developed dependingon insulin resistance related to oxidative stres contributes to the development ofcomplications.Paraoxonase (PON1) is an antioxidant enzyme closely associated withhigh-density lipoproteins. Low PON1 has been shown to be related withdyslipidemia, diabetes mellitus, advancing age, hypertension, level of lowHDL-cholesterol and increased oxidative stress. In this study, the subjects withmetabolic syndrome serum levels of PON 1 and ARE activities and totalcholesterol, triglyceride, LDL, HDL, VLDL, glucose, insulin, üric asid, C-peptid, AST, ALT, GGT and blood Hb, Htc, PLT levels are measured, and therelation between diagnostic criteria of metabolic syndrome and serum PON1activity levels was investigated and whether PON 1 activity is a part of MES ornot is investigated. The PON1 activity and phenotype has been demonstrated inmetabolic syndrome for the first time in this study.The serum PON1 activity in subject with metabolic syndrome has beenfound to be significantly lower ( p<0.05), and lipid concentrations significantlyhigher in subjects with the metabolic syndrome compared with unaffectedsubjects (p<0,05). Serum glucose, total cholesterol, LDL, VLDL, triglyceride,GGT, üric asid, insulin, C-peptid, BMI, systolic blood pressure and waistcircumference have been found to be significantly higher, and HDL-cholesterolto be significantly lower, in subjects with the metabolic syndrome comparedwith unaffected subjects (p<0.05). In determining the phenotype the ratio ofPON1/ARE activity has been fixed and thus the existence of 3 phenotype hasbeen shown.In summary, PON1 enzymatic activity which are lower antioxidant inthe subjects with metabolic syndrome, increased lipid levels, low HDL-cholesterol and increased glucose levels discovered significant correlate thatPON1 can hold an important place in the medical treatment an early diagnosisof metabolic syndrome.Key Words: Metabolic Syndrome, Paraoxonase, Arylesterase, Phenotype.
Investigation of paraoxonase 1 activities and phenotypes in patients with metabolic syndrome
Keywords: Biyokimya